Spectroscopic and Molecular Docking Studies on the Influence of Inulin on the Interaction of Sophoricoside with Whey Protein Concentrate - Anna Wang; Mengyang Xie; Ligen Wu (Foods)
The influence of inulin on the interaction of sophoricoside (Sop) with whey protein concentrate (WPC) was investigated using various spectroscopic methods, including fluorescence spectroscopy (intrinsic fluorescence, synchronous fluorescence, and three-dimensional fluorescence), ultraviolet-visible (UV–Vis) spectroscopy, Fourier transform infrared (FTIR) spectroscopy, and molecular docking. Sop was found to quench the intrinsic fluorescence of WPC by a static mechanism, both with and without the addition of inulin, and to enhance the antioxidant capacity of the protein. The addition of inulin slightly increased the binding distance between WPC and Sop, while reducing the number of binding sites from two to one. Non-covalent interactions, predominantly van der Waals forces and hydrogen bonding, were maintained between Sop and the protein. Synchronous fluorescence spectroscopy revealed that Sop prevents the exposure of hydrophobic groups on tryptophan residues, leading to increased surface hydrophilicity of the WPC complex. This aligns with the decreased protein surface hydrophobicity measured by 8-Anilino-1-naphthalenesulfonic acid (ANS) binding assays. With inulin, the overall hydrophobicity of the protein was lower than in the system without inulin, suggesting that both inulin and Sop improve the solubility of WPC. Three-dimensional fluorescence spectral analysis showed a reduction in fluorescence intensity and a red shift in the presence of both Sop and inulin. FTIR spectroscopy indicated a slight increase in the secondary structure ordering of WPC following the addition of both Sop and inulin, suggesting structural stabilization under heating conditions. Molecular docking highlighted the potential for hydrogen bond formation between Sop and WPC.